Voice and Letter: The First Made Last? - Zemke, John (2019)
The author argues that while all narratives, traditional or otherwise, are verbal, their strategies are mental. Oral traditions are neither more nor less than a particular hyponymy of language.
Keywords: narrative strategies; thought and literacy; verbalization; voice; the Great Divide